2003
DOI: 10.1021/ja028323d
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a PNA2−DNA2 Hybrid Quadruplex

Abstract: DNA guanine (G) quadruplexes are stabilized by an interesting variation of the hydrogen-bonding schemes encountered in nucleic acid duplexes and triplexes. In an attempt to use this mode of molecular recognition, we target a dimeric G-quadruplex formed by the Oxytricha nova telomeric sequence d(G(4)T(4)G(4)) with a peptide nucleic acid (PNA) probe having a homologous rather than complementary sequence. UV-vis and CD spectroscopy reveal that a stable hybrid possessing G-quartets is formed between the PNA and DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 61 publications
5
86
0
4
Order By: Relevance
“…An alternative strategy relies on sequence-based recognition, where complementary C-rich oligonucleotides bind via Watson-Crick base pairing to form heteroduplexes [7][8][9][10] or homologous G-rich oligonucleotides bind via Hoogsteen-based G-tetrad formation to yield heteroquadruplexes. [11][12][13][14][15] Peptide nucleic acid (PNA) probes can bind to G-quadruplexes by either of these mechanisms, leading to stable hybrid structures.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative strategy relies on sequence-based recognition, where complementary C-rich oligonucleotides bind via Watson-Crick base pairing to form heteroduplexes [7][8][9][10] or homologous G-rich oligonucleotides bind via Hoogsteen-based G-tetrad formation to yield heteroquadruplexes. [11][12][13][14][15] Peptide nucleic acid (PNA) probes can bind to G-quadruplexes by either of these mechanisms, leading to stable hybrid structures.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study by Datta and coworkers found that G 4 T 4 G 4 PNA and DNA oligonucleotides formed parallel Gquadruplexes with 1:1 DNA:PNA stoichiometry [20]. They also observed a drastic difference in CD spectra of their DNA and PNA complexes obtained by annealing at different temperatures.…”
Section: G 4 T 4 G 4 Pna and Dna Form Multiple Complexesmentioning
confidence: 90%
“…Under similar conditions without thermal annealing, Datta et al observed very similar CD spectra, which they interpreted to indicate the presence of antiparallel quadruplexes. At the same time, they demonstrated that fully equilibrated quadruplexes contained 2 PNA and 2 DNA molecules in a parallel orientation [20]. Therefore, DNA-PNA quadruplex complexes may not be limited to those with 1:1 stoichiometry, but can consist of different proportions of DNA and PNA strands with different strand orientation.…”
Section: G 4 T 4 G 4 Pna and Dna Form Multiple Complexesmentioning
confidence: 97%
“…1 H and 13 C NMR spectra were recorded on a Bruker Avance DRX 400 spectrometer at 400 and 100.6 MHz, respectively. Chemical shifts are reported as δ values (ppm) with reference to the residual solvent peaks.…”
Section: Methodsmentioning
confidence: 99%